7501 T > A mitochondrial DNA variant in a patient with glomerulosclerosis. (October 2014) - Imasawa, Toshiyuki; Tanaka, Masashi; Yamaguchi, Yutaka; Nakazato, Takashi; Kitamura, Hiroshi; Nishimura, Motonobu
Abstract The presence of granular swollen epithelial cells (GSECs) in tubular cells was recently reported to be a specific change associated with mitochondrial cytopathy. However, at present, GSEC is not routinely evaluated. We, in this study, present a case of glomerulosclerosis, in which the presence of GSECs should provide us one clue to understand the pathogenesis of its progressive decline of renal function. A 54-year-old Japanese female, who had been diagnosed with Graves' disease, was referred for the examination and treatment of her proteinuria (5.4 g/gCre at the first visit to our hospital). A kidney biopsy showed 28.6% of the glomeruli to be globally sclerosed and 10.7% of the glomeruli to have completely collapsed. However, according to a light microscopic analysis, all other glomeruli showed an almost normal appearance, except for some slight enlargement. Almost 30% of the interstitium was damaged by fibrosis. Characteristically, GSECs were observed in the medulla collecting ducts. Although she had no symptoms of either myopathy or encephalopathy, no history of stroke-like episodes or difficulty in hearing, her serum concentrations of lactate and pyruvate were both elevated. Therefore, mitochondrial DNA sequencing was performed to assess the etiopathogenesis of her nephropathy. Consequently, a homoplasmic 7501 T > A replacement, which has not been previously reported in patients with renal diseases, was detected. This case suggests that the routine evaluation of GSECs can provide important clues to assess the etiopathogenesis of cryptogenic glomerulosclerosis.